(untitled) (Dubuque, IA, 2006)
Annual Editions: Labor-Management Relations 05/06 was developed to show both the breadth and depth of the labor-management relations field not only in the United States, but around the world. It provides perspectives to students from the legal issues, the managerial view, the union's view, and global views.
Keywords: Industrial relations,Industrial relations,Quan hệ công nghiệp,Quan hệ công nghiệp; United States,Hoa Kỳ